Improvement of Very Shallow Soil by Hybridizing with Tank Silt: A Case Study from Osmanabad District, Maharashtra - P.H. Vaidya,; N.M. Patil,; S.P. Zade,; C.V. Ambadkar,; A.S. Dhawan, (Journal of the Indian Society of Soil Science, 2024)
Very shallow soil hybridized with tank silt recover the soil quality and productivity. Recycling of tank silt provides a win-win situation for improvement in soil health and renovation of the tank. The improvement of very shallow soil by hybridizing with tank silt, study was undertaken with quality of tank silt and its hybridizing effect on soil characteristics and yield of crops. The tank silts were found dark brown (10YR3/ 2) to black (10YR2.5/2) in colour, clay content varied from 48.7 to 76.3%, bulk density varied from 1.2 to 1.4 Mg m-3, hydraulic conductivity in between 0.75 to 3.4 cm h-1, high plant available water capacity (PWAC) > 250 mm, slightly to moderately alkaline (pH 7.3-8.1), electrical conductivity (EC)